2016
DOI: 10.1080/0092623x.2016.1141816
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Sexual Life and Changes Occurring in Sexual Life of Women With High-Risk Pregnancy

Abstract: This study was aimed at determining the quality of sexual life and changes occurring in the sexual life of women with high-risk pregnancy. The study was carried out at the obstetric clinic of a hospital in a province located in the Central Anatolia region of Turkey. The population of this cross-sectional study comprised 112 women diagnosed with high-risk pregnancy. When the period during which the women had a diagnosis of high-risk pregnancy was compared to the period during which they did not have such a diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
6
0
4
Order By: Relevance
“…Better counseling services that discuss the method of delivery are therefore required for mothers during their pregnancy, because after the proposed intervention and training, the trial group showed a greater satisfaction with their vaginal delivery and a better inclination to choose the same method for future pregnancies compared to the control group, which is indicative of the positive effects of the educational intervention on these two dimensions. The fact that this increase was not significant suggests the need for fundamental changes in the social infrastructure and the creation of a positive attitude toward vaginal delivery in society, which can be accomplished by the development and implementation of special programs (50–52). The mother’s feelings toward sexual relations was a dimension in which no significant differences were observed between the two groups after the intervention, even though both groups received higher scores in this dimension after the intervention (with the trial group’s scores being yet higher than the control’s).…”
Section: Discussionmentioning
confidence: 99%
“…Better counseling services that discuss the method of delivery are therefore required for mothers during their pregnancy, because after the proposed intervention and training, the trial group showed a greater satisfaction with their vaginal delivery and a better inclination to choose the same method for future pregnancies compared to the control group, which is indicative of the positive effects of the educational intervention on these two dimensions. The fact that this increase was not significant suggests the need for fundamental changes in the social infrastructure and the creation of a positive attitude toward vaginal delivery in society, which can be accomplished by the development and implementation of special programs (50–52). The mother’s feelings toward sexual relations was a dimension in which no significant differences were observed between the two groups after the intervention, even though both groups received higher scores in this dimension after the intervention (with the trial group’s scores being yet higher than the control’s).…”
Section: Discussionmentioning
confidence: 99%
“…No que tange ao aspecto sexual, embora a maioria das mulheres tenha referido atividade sexual durante a gestação, considerou-se alto o número de gestantes que negaram vida sexual ativa. Ao avaliar gestantes de alto risco na Turquia, evidenciou-se predominância de vida sexual prejudicada a partir do surgimento dos riscos na gestação (12) . As principais mudanças apontadas pelas mulheres foram diminuição da frequência de relações sexuais, menor desejo sexual, dor e sofrimento durante o ato, não considerar-se atraente e insatisfação sexual.…”
Section: Discussionunclassified
“…As principais mudanças apontadas pelas mulheres foram diminuição da frequência de relações sexuais, menor desejo sexual, dor e sofrimento durante o ato, não considerar-se atraente e insatisfação sexual. Percebeu-se que a condição de alto risco gestacional teve um efeito negativo sobre a vida sexual das mulheres (12) e, consequentemente, sobre a sua qualidade de vida. Nesse contexto, percebe-se a importância da educação sexual durante a gestação.…”
Section: Discussionunclassified
“…Sexual issues are more affected when pregnancy becomes a highrisk pregnancy, which can be regarded as the cause of reduced quality of sexual life. Besides, sex life is put on hold when pregnancy is highly risky [2]. Changes in sexual function accompany pregnancy and probably increasing the number of sexual problems when accompanied by particular disorders such as gestational diabetes [3].…”
Section: Introductionmentioning
confidence: 99%